Maps and Guidebooks: 17th-Century Prints in Modern Art History Studies - Arutyunyan, Julia I. (Actual Problems of Theory and History of Art, 2022)
17th-century maps acquire complex narrative frames: the image is combined with the expanded text. In the 17th century, in the European publishing practice, the form of guidebooks of various types has been formed, and a special place in their illustrative series is occupied by urban views, which represent a kind of scientific illustration. The graphic design of maps and guidebooks involves a complex compilation of the pictorial series, maps, landscape views, plans, schemes, and the combination of different types and styles of engravings. The choice of visual series is predetermined by the principle of selectivity and hierarchy of the attractions. The characteristic features of the graphic design of maps and guidebooks are the recognizability of the monuments, the generality of interpretation and schematism, the direct connection with the text, and the dialogue of visual and verbal components. The technique of etching prevails. The generality of the interpretation and the rejection of details are combined with the recognizability of silhouettes, stylistic transformations, and approximations to the aesthetic canons of modernity. The artist refers to the reflection of the realities of everyday life, to the genre approach in the interpretation. The circulation architectural graphics of the 17th century reflect the attitude of the epoch to space and time, interpreting it in the coordinates of the style. The large-scale body of works is united by the following characteristic features: the area is treated as a set of recognizable buildings, the buildings are classified by type, and a unified system of artistic techniques is developed: the panoramic nature of the space, the clarity of silhouettes, stylistic adaptation to the ideals of modernity, tendency towards narrativness, and the reflection of the realities of everyday life. The “inter-genre” nature of publications that combine maps, plans, landscapes, and images of specific structures is widespread, there is no single design principle or similar format, and the practice of using identical prints for different publications persists.
Keywords: history of art history; printed graphics of the 17th century; interdisciplinary approaches in art history; treatises on art of the 17th century; methodology of art history; architectural graphics; scientific illustration; landscape graphics; graphic travelogue; art of cartography; visual studies; veduta; graphic design of travel guides